Teching Children Arts: Towards Developing 21st Century Literacy Skills In Classrooms. - Nayanika Singh (2012)
Children are by nature creative. Involving them in aesthetic pursuits expands their creative horizons. Review of literature indicates that education in, through and about the arts enhances their cognitive engagement, value orientation, sensibility and expression of hidden talent. It also fosters a spirit of connectivity, equipping them sufficiently to become an empowered workforce of tomorrow. The present paper attempts to highlight the role of arts education in developing 21st century literacy skills among children in classrooms amidst the constantly evolving and challenging global scenario.